The effect of different energy sources on growth performance, abdominal fat depasition and fatty liver syndrome in broilers. ii. the effect on fatty liver syndrome - Şakir Doğan TUNCER; Reşat AŞTI; Behiç COŞKUN; Hüdaverdi ERER; Mehmet Ali TEKEŞ (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the effects of different energy sources used in broiler diets on occurence of fatty liver syndrome. Four hundred male and 400 femal dayold Arbro 7 were randomly distributed by sex into sixteen pens with each pen containing 50 chicks. In eight experimental rations, 1. Corn (M); 2. Sunflower oil (2.5 %) (AY1); 3. Sunflower oil (5 %) (AY2); 4. Fish oil (2.5 %) (BY1); 5. Fish oil (5 %) BY2); 6. Animal fat (2.5%) (HY1); 7. Animal fat (5%) (HY2); 8. Wheat + Sunflower oil (3 %) (BAY) were used as supplemental or based energy sources. Each ration was fed to one male and one female •group. Thus, sixteen groups were set up and experiment was ended at the 56th day. At the 56th day of the experiment, the highest liver weights and liver fat percentages of the male chickens were found in BY1 and BY2 fed fish oil. On the other hand, the highest liver weight was found in BY2 and the highest percentage of liver fat was observed in BY1 in the females. At the end of the experiment, in macroscopic investigation of livers of the male and female chickens fed fish oil were yellowish pale, swollen and crispy. In microscobic investigation of the livers in the same groups, the excessive amounts of lipid infiltrations were seen in the cytoplasma of paranchymal cells. Simiral observation was found in the livers of female chickens fed corn. There were the excessive amounts of lipid infiltrations in M and BAY in males and in HY1 and BAY females, but the lipid level was less than the above groups. By contrast, the lesser amounts of lipid infiltrations were observed in the liver paranchymal cells of the chickens fed the rations supplemented vegetable or animal fat. As a result, because of the best effect on the reduction of fat level obtained with supplementing various levels of sunflower oil, it is sug• gestecl that the vegetable oil be used in broiler rations as an energy substitute of some part of corn. On the contrary, fish oil used in broileı rations increasecl liver fat accumulation and caused fishy smell in meat.